2006
DOI: 10.1270/jsbbs.56.359
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two QTLs Controlling Resistance to Rice Stripe Virus Detected in a Japanese Upland Rice Line, Kanto 72

Abstract: The effects of two quantitative trait loci (QTLs) controlling the resistance to rice stripe virus (RSV) identified in a Japanese upland rice line, Kanto 72, (URK 72) were evaluated using near-isogenic lines (NILs). Two NILs carrying a single QTL (QTL-NILs) on chromosomes 2 and 11, respectively, were developed by markerassisted selection (MAS). The target QTL regions were introduced from the donor parent, Chugoku 40, which was bred from URK 72, into the genetic background of Koshihikari. Another line, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 13 publications
(21 reference statements)
3
31
0
Order By: Relevance
“…Previous mapping and allelic test suggested that both Stvb-i and Stvb are either tightly linked to or allelic with STV11 (refs 5, 8, 25). Intriguingly, our sequence analysis showed that Modan and Kanto 72, as well as their RSV-resistant offspring cultivars sequenced in this study all harbour the STV11-R allele (Supplementary Table 3), providing further support for their allelism.…”
Section: Resultsmentioning
confidence: 99%
“…Previous mapping and allelic test suggested that both Stvb-i and Stvb are either tightly linked to or allelic with STV11 (refs 5, 8, 25). Intriguingly, our sequence analysis showed that Modan and Kanto 72, as well as their RSV-resistant offspring cultivars sequenced in this study all harbour the STV11-R allele (Supplementary Table 3), providing further support for their allelism.…”
Section: Resultsmentioning
confidence: 99%
“…This method was successfully used to validate QTL when NILs were generated by backcrosses using one of the QTL mapping population parents as the recurrent parent (Wissuwa and Ae 2001;Maeda et al 2006;Delourme et al 2008). However, developing of NIL S by backcrossing is extremely laborious, especially in the case of soybean, because of the low successful hybridization rate.…”
Section: Introductionmentioning
confidence: 99%
“…Stva (St1) and Stvb (St2) are two complementary dominant major genes which confer RSV resistance (Washio et al, 1968a(Washio et al, , 1968b. A number of RSV resistance QTL have also been reported in recent years (Ding et al, 2004, Maeda et al, 1999, Ding et al, 2005, Wu et al, 2009; these were mapped to various rice chromosomes, but only two have been properly validated to date (Maeda et al, 2004(Maeda et al, , 2006. A number of RSV resistance QTL have also been reported in recent years (Ding et al, 2004, Maeda et al, 1999, Ding et al, 2005, Wu et al, 2009; these were mapped to various rice chromosomes, but only two have been properly validated to date (Maeda et al, 2004(Maeda et al, , 2006.…”
mentioning
confidence: 99%